A “hairy situation” in Minas Gerais, Brazil: a striking new species of Krenakanthus (Bromeliaceae: Bromelioideae) covered with uniseriate trichomes - Leme, Elton M. C.; Gonella, Paulo M.; Couto, Dayvid R.; Fernandez, Eduardo P.; Carvalho, Jordano D. T. De; Almeida, Pedro S. De; Mariath, Jorge E. A. (Phytotaxa, 2023)
A new species of Krenakanthus, a member of the bromelioid “Cryptanthoid complex”, is described based on plants discovered through collaborative citizen science. Krenakanthus ribeiranus and its only congener K. roseolilacinus are endemic to the “João Pinto Center of Biodiversity”, a still poorly explored region with Campos Rupestres and associated vegetation in the Rio Doce Valley, in eastern Minas Gerais state, Brazil. The unusual combination of morphological characters of K. ribeiranus, highlighted by plant delicacy and almost all leaf and flower parts covered by uniseriate, hair-like trichomes, is illustrated and discussed in comparison with K. roseolilacinus, including leaf and seed anatomy, as well as pollen morphology. This micro-endemic species is assessed as Critically Endangered, reinforcing the need for strategy to protect the biodiversity of the region. The morphology of the new species validates and strengthens the diagnostic flower characters used in the circumscription of Krenakanthus, suggesting as secondary diagnostic characters the habit, stature, and leaf conformation.